(untitled) (Homiletic, 2012)
Despite the historical connection between intoned black preaching and the creation and performance of the Negro spirituals, there is silence in homiletical literature about how the spirituals may serve as a resource for the theory and practice of preaching today. This article argues that the spirituals as musical sermons can be a helpful homiletical resource for thinking about preaching, death, and hope, particularly in highlighting the critical relationship between death and the proclamation of the gospel. In light of prosperity gospel preaching and other forms of proclamation that deny the critical role of death in preaching Christian hope, the spirituals offer a healthy and constructive way forward. Thus, remembering them can help re-member preaching.